Development of a Chemiluminescence Immunoassay for Quantification of 25-Hydroxyvitamin D in Human Serum - Shuang Han; Wuxian Qiu; Junlan Zhang; Zhonghu Bai; Xiao Tong (Journal of Analytical Methods in Chemistry)
In this study, a chemiluminescence immunoassay (CLIA) for human serum 25-hydroxyvitamin D (25(OH)D) was established by a competition model. In serum, more than 99% of total circulating 25(OH)D binds to protein and less than 1% of 25(OH)D is in free form (Jassil et al., 2017). Before measuring concentration of 25(OH)D in serum, a releasing procedure should be conducted. A new reagent is used to release binding 25(OH)D to free form. Streptavidin (SA) was labeled to magnetic beads by a 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS) method. Biotinylated VD was used as a competitor of 25(OH)D in samples. Anti-VD antibody (aby) was labeled to horseradish peroxidase (HRP) by EDC to react with 25(OH)D and biotinylated-VD molecules. The pretreated samples or standards were added into the reaction tube with biotin-VD and anti-VD aby-HRP, free 25(OH)D in the sample competes with biotinylated VD for binding to anti-VD aby-HRP, an SA-labeled magnetic particle is added to isolate the signal-generating complex, and the signal is inversely proportional to the 25(OH)D concentration in the sample. The method established shows good thermostability and performance. The limitation of detection (LoD) is 1.43 ng/mL. The intra-assay coefficient of variation (CV) is 3.66%–6.56%, the interassay CV is 4.19%–7.01%, and the recovery rate is 93.22%–107.99%. Cross-reactivity (CR) was remarkably low with vitamin D2, vitamin D3, 1, 25-dihydroxyvitamin D3, and 1, 25-dihydroxyvitamin D2. At the same time, the cross-reaction values with 25-hydroxyvitamin D2 and 25-hydroxyvitamin D3 were 97% and 100%, respectively. The developed method shows good correlation with the total VD product from Roche and DiaSorin. 1096 clinical patient samples were measured with developed reagent kit in this study. 7 types of disease were involved, and the concentration of 25(OH)D is less than 30 ng/mL in 94.98% of patients.